2000
DOI: 10.1515/dmdi.2000.16.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Tea on Lipid Peroxidation in Carbon Tetrachloride Treated Male Rats

Abstract: This study examined the effects of black tea (Camellia sinensis L.) on lipid peroxidation and glutathione levels in carbon tetrachloride (CCl4)-treated male Wistar rats. Three groups of rats formed two control groups and one treatment group. The control groups were fed with a standard diet, while the black tea group were fed the standard diet plus 6% by weight dried black tea leaves. After two months, the rats in the black tea group and in one control group were administered a single dose of CCl4 (1 ml/kg, i.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Administration of tea and tea polyphenols was previously reported to prevent or attenuate decreases in levels of tissue GSH in a number of animal models. [39][40][41] In addition, it bears notice that EGCG was used at 50 mM in our experiments, which was much lower than that of NAC (5 mM) used (Figures 7-10). However, the phyto-chemical showed a similar ability, if not higher, to increase the level of cellular GSH and to interrupt TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of tea and tea polyphenols was previously reported to prevent or attenuate decreases in levels of tissue GSH in a number of animal models. [39][40][41] In addition, it bears notice that EGCG was used at 50 mM in our experiments, which was much lower than that of NAC (5 mM) used (Figures 7-10). However, the phyto-chemical showed a similar ability, if not higher, to increase the level of cellular GSH and to interrupt TGF-b signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Tea (Camellia sinensis), the most commonly consumed beverage in the world, is a rich source of polyphenolic compounds (Beecher et al, 1999;Blazovics et al, 2003), known as the tea flavonoids. Tea polyphenols possess strong antioxidative properties (Azam et al, 2004;Chen et al, 2004;Mandel et al, 2004), antilipid peroxidation capacity (Sur-Altiner and Yenice, 2000) and are excellent chemopreventors against reactive oxygen and nitrogen species (Sarkar and Bhaduri, 2001). Tea extracts also increases antioxidant parameters (Leenan et al, 2000;Luczaj and Skrzydlewska, 2005) and its aqueous extract has been shown to quench reactive oxygen species such as singlet oxygen, superoxide and hydroxyl radicals (Thiagarajan et al, 2001;Wei et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that green tea administration can reduce lipid peroxidation in diabetic animals (Yamaguchi et al, 1991;Tijburg et al, 1997;Vinson et al, 1998;Miura et al, 2001;Guleria et al, 2002;Kasaoka et al, 2002;Liuji et al, 2002;Sabu et al, 2002;Skrzydlewska et al, 2002;. Black tea has been reported to be an efficient reducer of peroxidation of lipoproteins as well Vinson et al, 1998;Sur-Altiner et al, 2000;Yokozawa et al, 2002;Vinson et al, 2005;Alipoor et al, 2008). Some studies have investigated the effects of purified tea polyphenols and drawn similar results (Quine et al, 2005;Yamabe et al, 2006).…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%